Pixels Beyond Colors: Exploring Attributes and Representations of Text-Art Images - Bueno, João Sebastião de Oliveira (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware), 2023)
Due to historical factors and hardware limitation, printed characters have been around to represent images in digital computers for longer than pixel-based raster images exist. With modern hardware and an enrichment of available characters the expressiveness of possible forms of image representation with characters should’ve grown as an art form. However, the modern use of character-based images as a digital art-form is comparatively small. This work revisits the history of graphic displays, and points to the absence of a widely accepted way to create, store and transmit character-based images using several text-based image capabilities as one of the factors that may be delimiting this expression. It then moves towards proposing techniques and terminology to make these more widespread.